2002
DOI: 10.1017/s0022112001006516
|View full text |Cite
|
Sign up to set email alerts
|

Density-driven instabilities of miscible fluids in a Hele-Shaw cell: linear stability analysis of the three-dimensional Stokes equations

Abstract: We consider the situation of a heavier fluid placed above a lighter one in a vertically arranged Hele-Shaw cell. The two fluids are miscible in all proportions. For this configuration, experiments and nonlinear simulations recently reported by Fernandez et al. (2002) indicate the existence of a low-Rayleigh-number (Ra) ‘Hele-Shaw’ instability mode, along with a high-Ra ‘gap’ mode whose dominant wavelength is on the order of five times the gap width. These findings are in disagreement with linear stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
50
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 40 publications
15
50
5
Order By: Relevance
“…the local concentration of NaI in fingers was higher when the initial interface thickness was thin. The experimental results were consistent with the LSA results for a Hele-Shaw cell (Fernandez et al 2002;Graf et al 2002;Lajeunesse et al 1997) and viscous fingering (Manickam and Homsy 1995;Tan and Homsy 1986); the wavelength and amplification factor decreased with interface thickness. The case of thicker initial interface, for example = 23.4 mm, only one finger occurred and extended downward because of the scale of the packed bed.…”
Section: Finger Number Densitysupporting
confidence: 85%
See 3 more Smart Citations
“…the local concentration of NaI in fingers was higher when the initial interface thickness was thin. The experimental results were consistent with the LSA results for a Hele-Shaw cell (Fernandez et al 2002;Graf et al 2002;Lajeunesse et al 1997) and viscous fingering (Manickam and Homsy 1995;Tan and Homsy 1986); the wavelength and amplification factor decreased with interface thickness. The case of thicker initial interface, for example = 23.4 mm, only one finger occurred and extended downward because of the scale of the packed bed.…”
Section: Finger Number Densitysupporting
confidence: 85%
“…Heller (1966) demonstrated that the amplification factor decreased with Rayleigh number Raδ with the thickness of interface as characteristic length by a LSA for porous media. Using LSA, Graf et al (2002) showed that the amplification factor (the maximum eigenvalue) for a Hele-Shaw cell decreased with increasing interface thickness. Tan and Homsy (1986) used QSSA to determine that the amplification factor and wave number decreased with time (i.e., diffusion of the interface for viscous fingering).…”
Section: Onset Timementioning
confidence: 99%
See 2 more Smart Citations
“…1 In a gravity field, if the more dense fluid lies on top of the less dense one, the horizontal interface is buoyantly unstable because of a RayleighTaylor instability and related "density fingering" can be observed. [2][3][4] In vertical displacements, such viscous and buoyancy effects can either cooperate to stabilize or destabilize the flow 5 or, on the contrary, compete, in which case there is a critical injection velocity above which there is an instability. 1 In horizontal systems, the density jump is in the direction perpendicular to gravity and the stability of the interface is classically considered to depend only on the viscosity difference: viscous fingering can be observed when the less viscous fluid is injected into the more viscous one while the reverse displacement is viscously stable.…”
Section: Introductionmentioning
confidence: 99%